Developing smallholder value chains – Kenya. Project profile. - International Potato Center (2019)
Agriculture continues to dominate Kenya’s economy, accounting for one third of GDP and employing 75% of the rural population. Maintaining growth and accelerating development in this important sector will require largescale adoption of productivity-enhancing technologies and innovations. This project supports increased food and nutrition security and higher incomes for everyone involved in specific agricultural value chains, making a significant contribution to more inclusive economic development.